Biological Evaluation of Halogenated Thioureas as Cholinesterases Inhibitors Against Alzheimer’s Disease & Molecular Modeling Studies - Iqbal, Jamshed; Zaib, Sumera; Saeed, Aamer; Muddassar, Muhammad (Letters in Drug Design & Discovery, 2015)
Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibition is thought to be an encouraging approach towards the therapy of Alzheimer’s disease (AD). The current paper targets to give a concise information of mono and dihalo- substituted thioureas similarity with anti-AD potential. The present results represent evaluation of cholinesterase inhibitory potential for halogenated thioureas derivatives. Compound 1t was constituted to be highly potent inhibitor with Ki value 0.12 ± 0.05 µM against AChE, while 1b was most the active inhibitor for BChE with Ki value of 0.03 ± 0.001 µM. Molecular docking simulations were performed using the homology models of both cholinesterases in order to explore the plausible binding modes of synthesized compounds.
Keywords: halogenated thioureas